Asymmetric Catalytic [2, 3] Stevens and Sommelet–Hauser Rearrangements of α‐Diazo Pyrazoleamides with Sulfides. (12th August 2019) - Lin, Xiaobin; Yang, Wei; Yang, Wenkun; Liu, Xiaohua; Feng, Xiaoming
Abstract: Catalytic enantioselective [2, 3] Stevens and Sommelet–Hauser rearrangements of α‐diazo pyrazoleamides with sulfides were achieved by utilizing chiral N, N ′‐dioxide/nickel( II ) complex catalysts. These rearrangements proceeded well under mild reaction conditions, providing rapid and facile access to a series of functionalized 1, 6‐dicarbonyls or sulfane‐substituted phenylacetates with high to excellent enantioselectivities. The catalytic system shows excellent stereocontrol, discriminating between the heterotopic lone pairs of sulfur and controlling both the 1, 3‐proton transfer and the [2, 3]‐σ rearrangement. Abstract : Kontrollpunkte : Chirale N, N′ ‐Dioxid/Ni II ‐Komplexe katalysieren effizient die asymmetrischen katalytischen [2, 3]‐Stevens‐ und Sommelet‐Hauser‐Umlagerungen von α‐Diazopyrazolamiden mit Sulfiden. Das katalytische System zeigt eine ausgezeichnete Stereokontrolle, die zwischen den heterotopen freien Elektronenpaaren des Schwefels diskriminiert und sowohl den 1, 3‐Protonentransfer als auch die [2, 3]‐σ‐Umlagerung steuert.